Measuring regional inequality by internet car price advertisements: Evidence for Germany - Konstantin A. Kholodilin; Boriss Siliverstovs (ETH Zurich, KOF Swiss Economic Institute, 2010)
We suggest to use Internet car sale price advertisements for measuring economic inequality between and within German regions. Our estimates of regional income levels and Gini indices based on advertisements are highly, positively correlated with the official figures. This implies that the observed car prices can serve as a reasonably good proxy for income levels. In contrast to the traditional measures, our data can be fast and inexpensively retrieved from the web, and more importantly allow to estimate Gini indices at the NUTS2 level - something that never has been done before. Our approach to measuring regional inequality is a useful alternative source of information that could complement the officially available measures.
Keywords: C21; O47; R11; 330; Car price advertisements; economic inequality; German NUTS1 and NUTS regions; Gini index; Internet; Kraftfahrzeug; Preis; Internet; Regionale Disparität; Gini-Koeffizient; Deutschland